ICT Impact on Job Satisfaction Among School Teachers with Reference to West Singhbhum, Chakradharpur (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The importance of education has increased due to the growth of information and the specialisation of jobs brought about by scientific and technical advancements. Racial shift affects the whole social structure. This study will combine exploratory and descriptive research methods, drawing heavily on primary and secondary sources of information. According to the instructors' feedback, ICT training had a profound effect on their outlook and competence. Nevertheless, it was emphasised that trainings should be highly applicable to teachers' requirements and tied to classroom practices within the larger system of educational organisation. This includes factors like time, curriculum, resources, and environment.